Clinical efficacy and safety of the tablets Mipranol for Dogs in the prevention and treatment of helminth infections - Feshchenko, D.; Dovhiy, Yu.; Berezovskyi, A.; Zghozinska, O. (Scientific Progress & Innovations, 2025)
Clinical trials of a production batch of the anthelmintic veterinary drug Mipranol for Dogs (tablets, with active ingredients milbemycin oxime and praziquantel) were conducted on target animals (dogs). The aim was to evaluate the therapeutic and antiparasitic efficacy, as well as the safety of the drug, in treating dogs affected by cestodes (Dipylidium caninum, Taenia spp., Echinococcus spp., Mesocestoides spp.) and nematodes (Ancylostoma caninum, Toxocara canis, Toxascaris leonina, Trichuris vulpis, Thelazia callipaeda, Angiostrongylus vasorum, Crenosoma vulpis, Dirofilaria immitis), including mixed nematode-cestode infections. The studies involved adult dogs (n=170) with clinically and laboratory-confirmed spontaneous infections caused by gastrointestinal and pulmonary parasites, including Thelazia callipaeda. Separate trials were also conducted on healthy animals (n=12) to assess the preventive effect of the drug against heartworm disease. The studies demonstrated high therapeutic efficacy (100 %), safety, and an absence of side effects of the drug on dogs. Two species of nematodes, A. vasorum and Th. callipaeda, were exceptions to the absolute anthelmintic effect of the product. In these cases, while the clinical condition of the affected animals improved, the intensity of invasion decreased to 25.9 % and 21.6 %, respectively, compared to the initial levels. The efficacy of the drug as a prophylactic agent against heartworm disease in dogs was also confirmed. Monthly administration of Mipranol for Dogs during the active blood-sucking insect season in endemic regions protected animals from developing clinical heartworm disease by eliminating microfilariae inoculated into the bloodstream. The use of Mipranol for Dogs (manufactured by BROVAFARMA LLC) at the recommended doses and administration intervals provides sufficient nematocidal and cestocidal efficacy against the target helminth species in dogs. The developed drug proved to be a safe anthelmintic agent, causing no adverse or side effects in adult dogs during or after oral administration.